Management challenges in primary hyperoxaluria type 1 with end-stage kidney disease: A case report - Mahdi Awwad; Nasim Afif AbuKaresh; Hamza A. Abdul-Hafez; Ma'moun Qawasmeh; Mohanad Jaber; Ahmad Thiab Albaw; Mohammad Alnees (Transplantation Reports)
Introduction and importance: Primary hyperoxaluria (PH) is a metabolic condition that leads to oxalate production, resulting in kidney failure and oxalate nephropathy. Posttransplant mobilization of oxalate poses a risk of recurrence. This case emphasizes the importance of measures in cases of end-stage kidney disease (ESKD) with unknown origins. Case presentation: A 53-year-old man with a history of hypothyroidism, recurring kidney stones, and a family background of renal disease and stomach cancer presented with high blood pressure and elevated creatinine levels (2 mg/dL). A subsequent renal biopsy confirmed PH1. Despite initiating hemodialysis, his kidney function deteriorated, necessitating a liver and kidney transplant. Following the transplant, the patient developed lymph node enlargement. Experienced humoral rejection, leading to the resumption of hemodialysis. Clinical discussion: The case discussion highlights the treatment complexities associated with PH1, emphasizing the importance of detection and vigilant monitoring post transplantation and multidisciplinary care for managing complications effectively. Conclusion: Early detection, thorough diagnostics, and customized posttransplant care play roles in managing hyperoxaluria. Future research should focus on enhancing methods, refining transplantation techniques, and developing strategies to prevent and manage complications effectively.